Valuation of primers for the detection of hiv-1 viruses from Kelantan by using reverse transcription polymerase chain Reaction (RT-PCR) - Minal, Noor Hamizah (Universiti Sains Malaysia, 2013)
Human immunodeficiency virus type 1 (HIV-1) has been recognized as the causative agent of acquired immunodeficiency syndrome (AIDS). Approximately 42 million people carrying the virus at present, but its case fatality rate is close to 100%, making it an infection of devastating ferocity. Since the evolutionary change of the virus is at rapid rate, it imposes a challenge on HIV diagnostic development, vaccine development, antiretroviral drug sensitivity and drug resistance. Rapid and sensitive methods for the detection of HIV-1 viruses would be valuable in controlling this disease. Currently, nucleic acid amplification tests such as reverse transcription polymerase chain reaction (RT-PCR) and real-time PCR (rtPCR) are widely used in detecting HIV-1 viruses. These tests are commonly applied in blood donation screening and early detection of HIV-1 in infants. High sequence variations of the HIV-1 viruses from Kelantan have led to the failure to obtain the amplification product using published primers. Therefore, in this study, a few set of primers were designed based on the sequence alignments of published HTV-1 viruses from Malaysia and Kelantan which were retrieved from NCBI genebank. The primers were evaluated on 30 confirmed HIV-1 positive samples from Kelantan, Malaysia. HIV LTRF2 and HIV LTR2 were chosen as the best primers to detect these viruses since they were successfully amplified all the 30 samples used in this study. The primers were further evaluated their sensitivity and specificity against 3 viruses which are Japanese encephalitis (JE), Chikungunya and Western encephalitis virus (WEE) where no expected band yielded. These primers were sensitive and specific enough in detecting HIV-1 viruses from Kelantan. They were further evaluated for use in the real-time PCR and can be used in this test. Thus, these primers could be potentially use for the future diagnosis of HIV-1 viruses from Kelantan either by conventional or real time PCR.